Analisis dan Perbaikan Sistem Kompensasi pada UKM XYZ Kota Cilegon dengan Metode Dua Titik - Edly Naufaldy Rahman; Hana Putri Pertiwi; Najmah Nurlaila Hasna; Zahra Uhastaning Kinasih; Lindawati Kartika (Syntax Idea)
Every company has an obligation to provide wages to employees in accordance with the provisions. The provision of wages according to the standard aims to ensure that workers earn an income that can meet the needs of a decent life. The compensation system is considered important in an organization because it has a direct impact on employee motivation and performance. This study aims to assess the compensation system in UKM XYZ in Cilegon City, which is engaged in the culinary sector, and provide recommendations for improving the compensation system. The methods used in this study are determining job value based on compensation factors using the Hay method, determining job grading using the given grade and minimum maximum methods, and salary mapping using the two-point method. The results obtained from this study indicate that the compensation system in the form of salary at UKM XYZ is still not ideal because it is below the minimum wage and there is no job grading determination yet. There are ten compensable factors needed in determining the compensation system for UKM XYZ. Improvements were made by calculating job values and dividing job titles into four grades. Based on salary mapping for a more ideal compensation system, the results show that salary mapping using the two-point method can be considered by SMEs for future implementation because it already meets the minimum wage and is adjusted to the budget of UKM XYZ.